2023
DOI: 10.3390/ijms24065742
|View full text |Cite
|
Sign up to set email alerts
|

The Tryptophan and Kynurenine Pathway Involved in the Development of Immune-Related Diseases

Abstract: The tryptophan and kynurenine pathway is well-known to play an important role in nervous, endocrine, and immune systems, as well as in the development of inflammatory diseases. It has been documented that some kynurenine metabolites are considered to have anti-oxidative, anti-inflammatory, and/or neuroprotective properties. Importantly, many of these kynurenine metabolites may possess immune-regulatory properties that could alleviate the inflammation response. The abnormal activation of the tryptophan and kynu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…Furthermore, the tryptophan metabolism was selectively upregulated in NASH leading to increased levels of tryptophan, kynurenine and Indoleacrylic acid ( Figure 7 A,B). Because kynurenine and its metabolites have immunosuppressive effects [ 18 ], we determined the immune response in these mice. Therefore, we used the MELC technology for high-content immunohistochemistry, which was used to visualize 30 antibodies ( Supplementary Table S4 ) describing the major immune cell types [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the tryptophan metabolism was selectively upregulated in NASH leading to increased levels of tryptophan, kynurenine and Indoleacrylic acid ( Figure 7 A,B). Because kynurenine and its metabolites have immunosuppressive effects [ 18 ], we determined the immune response in these mice. Therefore, we used the MELC technology for high-content immunohistochemistry, which was used to visualize 30 antibodies ( Supplementary Table S4 ) describing the major immune cell types [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lot of previous studies reported that Trp metabolites act as AhR agonists [ 19 , 20 , 33 , 41 , 42 ]. The primary Trp metabolism is known to be the kynurenine pathway that accounts for greater than 90% of the peripheral metabolism of Trp in mammals [ 43 , 44 ], and Trp is metabolized to Kyn via its metabolizing enzyme, indoleamine 2,3 dioxygenase (IDO)-1, which is reported to affect the Th17/Treg balance [ 32 ]. This increase in Kyn was reported to lead to an increase in Tregs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is mainly broken down through the kynurenine pathway, which donates electrons to the tricarboxylic acid (TCA) cycle and converts a significant portion of the tryptophan into various bioactive metabolites [ 55 , 56 ]. These metabolites are suspected to have antioxidant, anti-inflammatory, and/or neuroprotective properties [ 57 , 58 , 59 , 60 ]. Hypoxia could alter the activity of the kynurenine pathway, potentially affecting tryptophan metabolism and its downstream effects on improving immune function and neuronal health in OHT patients.…”
Section: Discussionmentioning
confidence: 99%